Interactive Firefighter Trainer - Rasulovich, Khaldorov Azizjon; Atamirzaevich, Khodjaev Abdugani (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article, the newly opened "Simulation innovative training centers" in the educational and training institutions of the Ministry of Emergency Situations, Health and other ministries of the Republic of Uzbekistan, about some types of modern interactive simulators and simulators available in them, as well as the knowledge and skills of the personnel of firefighting and rescue structures. information about the interactive training simulator "MKP-02/OG", which is an effective training tool for development work.